Antiretroviral Therapy Adherence Interruptions are Associated with Systemic Inflammation among Ugandans who Achieved Viral Suppression - Musinguzi, Nicholas; Jose, Castillo-Mancilla; Morrow, Mary; Byakwaga, Helen; Mawhinney, Samantha; Burdo, Tricia H.; Boum, Yap; Muzoora, Conrad; Bwana, Bosco M.; Siedner, Mark J.; Martin, Jeffrey N.; Hunt, Peter W.; et al. (Journal of acquired immune deficiency syndromes, 2019)
Background: Residual systemic inflammation, which is associated with non-AIDS clinical outcomes, may persist despite viral suppression. We assessed the effect of antiretroviral (ART) adherence interruptions on systemic inflammation among Ugandans living with HIV who were virally suppressed. Setting; We evaluated adults initiating first-line ART at a regional referral hospital clinic in Mbarara, Uganda. Methods: Plasma concentrations of interleukin-6 (IL-6), D-dimer, soluble sCD14, sCD163, the kynurenine/tryptophan (K/T) ratio, and CD8+ T-cell activation (HLA-DR+/CD38+ co-expression) were measured at baseline and 6 months following ART initiation among participants who achieved viral suppression (VL<400) at 6 months. ART adherence was monitored electronically. Time spent in an adherence interruption was computed as the percentage of days when the running average adherence was ≥10%. We fit adjusted linear regressions to evaluate the effect of time spent in an interruption on the log-transformed plasma concentrations of the inflammation biomarkers. Results: Of 282 participants, 70% were female and median age was 34 years. At baseline, median CD4 and median log viral load were 135 cells/μl and 5.1 copies/ml, respectively. In the adjusted analysis, a running average adherence <10% was associated with higher sCD14 (+3%, p<0.008), sCD163 (+5%, p=0.002), D-dimer (+10%, p=0.007), HLA-DR+/CD8+ (+3%, p<0.025), IL-6 (+14%, p=0.008), and K: T ratio (+5%, p=0.002). These findings were largely robust to adjustment for average adherence, as well as higher thresholds of running average adherence, albeit with decreased statistical significance. Conclusion: Increased time spent in adherence interruptions is associated with increased levels of inflammation despite viral suppression above and beyond average adherence.
Keywords: Adherence; Treatment interruption; Inflammation; Antiretroviral therapy; Uganda